2016
DOI: 10.1039/c5tb02482j
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticle based coatings enhance adipogenesis compared to osteogenesis in human mesenchymal stem cells through oxidative stress

Abstract: Silver nanoparticle based coatings preserve the osteogenesis capacity while promoting the adipogenesis of human mesenchymal stem cells through oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…Immunofluorescent staining was conducted according to a previous report 25 to evaluate the expression of osteogenic marker proteins, including COLI, OPN (on day 7 after induction), and OCN (on day 14 after induction). Briefly, the cells were washed twice with PBS, fixed with 4% (w/v) paraformaldehyde for 30 min, and then permeabilized with 0.2% Triton X-100 for 5 min.…”
Section: Expression Of Type I Collagen (Coli) Osteopontin (Opn) and mentioning
confidence: 99%
“…Immunofluorescent staining was conducted according to a previous report 25 to evaluate the expression of osteogenic marker proteins, including COLI, OPN (on day 7 after induction), and OCN (on day 14 after induction). Briefly, the cells were washed twice with PBS, fixed with 4% (w/v) paraformaldehyde for 30 min, and then permeabilized with 0.2% Triton X-100 for 5 min.…”
Section: Expression Of Type I Collagen (Coli) Osteopontin (Opn) and mentioning
confidence: 99%
“…In a pioneering study we demonstrated the mammalian cells can tolerate greater amount of silver than bacteria. Our nding was also conrmed by others and our follow up studies 3,6,12 which showed that amounts of silver lethal to bacteria did not signicantly affect primary human broblasts and mesenchymal stem cells (MSCs). However, mammalian cells may have different tolerance to silver and our current study demonstrate that, although capable of recovery, the viability of mKSCs was reduced in the early stages of growth.…”
Section: Effect Of Silver Nanoparticle Concentration On Mksc Viabilitmentioning
confidence: 61%
“…The reduced initial viability and attachment of the cell on the silver containing samples could be due to the substantial amount of released silver ions from the surfaces. 6,12 The silver ions are the active species that make silver such a potent antibacterial agent but the element could be toxic to mammalian cells too. In a pioneering study we demonstrated the mammalian cells can tolerate greater amount of silver than bacteria.…”
Section: Effect Of Silver Nanoparticle Concentration On Mksc Viabilitmentioning
confidence: 99%
See 2 more Smart Citations